2015
DOI: 10.1182/blood-2015-03-634428
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 loss in hematopoietic stem cells predisposes mice to develop heterogeneous malignancies in an Ezh1-dependent manner

Abstract: Key Points Ezh2 loss in hematopoietic stem cells predisposes mice to develop heterogeneous hematologic malignancies. Ezh1 is essential to maintain hematopoiesis in the setting of Ezh2 loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 55 publications
6
121
1
Order By: Relevance
“…35,36 In contrast, deletion of Ezh2 in mouse hematopoietic compartments results in T-cell acute leukemia 37 and MDS-like phenotype. 38 Furthermore, loss of Ezh2 cooperates with Tet2 deficiency 39 or RUNX1 mutation 40 in the development of MDS. Interestingly, Ezh2 knock-in mice overexpressing Ezh2 in hematopoietic cells develop MPN-like disease.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In contrast, deletion of Ezh2 in mouse hematopoietic compartments results in T-cell acute leukemia 37 and MDS-like phenotype. 38 Furthermore, loss of Ezh2 cooperates with Tet2 deficiency 39 or RUNX1 mutation 40 in the development of MDS. Interestingly, Ezh2 knock-in mice overexpressing Ezh2 in hematopoietic cells develop MPN-like disease.…”
Section: Discussionmentioning
confidence: 99%
“…This functional duality of Ezh2 has also been demonstrated in experiments in mouse models. Several experiments in which mice were observed long-term after loss of Ezh2 in hematopoietic cells showed that this loss leads to development of heterogeneous malignancies including T-ALL, MDS, and MDS/MPN [84][85][86]. These results indicate that Ezh2 functions as a tumor suppressor gene in the pathogenesis of T-ALL and MDS-related diseases.…”
Section: Prc2 Members In Hematological Malignanciesmentioning
confidence: 93%
“…Ezh2-deficient hematopoietic cells develop MDS and MDS/MPN-like diseases in mice, but not AML even in serially transplantation [9,37], implying an oncogenic property of EZH2 in the pathogenesis of AML. In fact, deletion of Ezh2 resulted in significantly reduced leukemia-initiating cells and enhanced differentiation of leukemic cells in a mouse model of MLL-AF9 induced AML.…”
Section: Oncogenic Function Of Ezh2 In De Novo Amlmentioning
confidence: 96%
“…In contrast, Ezh2 is dispensable for self-renewal of HSCs due to the compensatory function of Ezh1. Ezh1-containing PRC2 (Ezh1-PRC2) co-regulates a large number of target genes with Ezh2-containing PRC2 (Ezh2-PRC2) and, notably, is redistributed to a significant portion of Ezh2-specific targets on the loss of Ezh2 [7,9,10]. On overexpression, Ezh2 efficiently prevents exhaustion of the long-term repopulating potential of HSCs during repeated serial transplantation [11].…”
Section: Epigenetics In Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation